2017
DOI: 10.21577/1984-6835.20170043
|View full text |Cite
|
Sign up to set email alerts
|

The Grätzel Solar Cell: A Proposal for Interdisciplinary Experimentation

Abstract: In this article an experimental work was evaluated to explore and disseminate solar energy thematic in an interdisciplinary way to different undergraduate courses. Initially the work was proposed as an activity of a post-graduation discipline for master and doctorate students. From this activity, it was applied an experiment on dye-sensitized solar cells, evaluated in different undergraduate courses in the form of short courses. Dye-sensitized solar cells were mounted by students, to better understand the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…Fan et al, 17 reported nanosphere formation from this production method using others precursors, specifically hexamethylenetetramine, (CH 2 ) 6 N 4 , zinc nitrate (Zn(NO 3 ) 2 ), and Na 3 C 6 H 5 O 7, as a surfactant. 18 The TiO 2 particles did not exhibit a well-defined morphology, instead of taking the form of clusters. According to Costa et al, 19 Pratsinis, 20 and Hong et al, 21 particles smaller than 1 μm tend to agglomerate because of the high surface energy associated with the extensive surface area of such small particles.…”
Section: Figures 4 and 5 Shows The X-ray Diffractograms Of Tio 2 And mentioning
confidence: 96%
“…Fan et al, 17 reported nanosphere formation from this production method using others precursors, specifically hexamethylenetetramine, (CH 2 ) 6 N 4 , zinc nitrate (Zn(NO 3 ) 2 ), and Na 3 C 6 H 5 O 7, as a surfactant. 18 The TiO 2 particles did not exhibit a well-defined morphology, instead of taking the form of clusters. According to Costa et al, 19 Pratsinis, 20 and Hong et al, 21 particles smaller than 1 μm tend to agglomerate because of the high surface energy associated with the extensive surface area of such small particles.…”
Section: Figures 4 and 5 Shows The X-ray Diffractograms Of Tio 2 And mentioning
confidence: 96%
“…Enciso et al [21] used open-source microcontrollers and DSSCs to help students learn basic principles from practical applications. Mayrinck et al developed an interdisciplinary undergraduate course that focused on a hands-on experiment using a DSSC module [24] We incorporated DSSCs into teaching modules in which students could use screen printing technology to connect DSSCs in parallel to increase current flow. Students could thus make their own DSSCs that were capable of powering a small fan motor.…”
Section: Hands-on Dssc Experimentsmentioning
confidence: 99%
“…In transdisciplinary research, investigators step outside the boundaries of their known areas of inquiry to create a separate intellectual space. Within an interdisciplinary space, researchers inform each other's perspectives and compare results through the transfer of knowledge across disciplines [23][24][25]. The hands-on DSSC course addresses two major aspects (Figure 3).…”
Section: Interdisciplinary Course Designmentioning
confidence: 99%
See 2 more Smart Citations